Auditory script location does not affect acquisition and maintenance of vocal initiations by children with autism. (20th December 2016) - Gallant, Emily E.; Reeve, Sharon A.; Brothers, Kevin J.; Reeve, Kenneth F.
Abstract : The present study evaluated whether two different locations of auditory scripts, relative to target discriminative stimuli, affected acquisition and maintenance of initiations of vocal interactions by four boys with autism or pervasive developmental disorder not otherwise specified. An alternating‐treatments design with an initial baseline was used. Button‐activated recording devices used to play the scripts were placed either on target stimuli or held behind the participants' heads to initiate interactions about a variety of toys. After scripts and the devices were faded, the frequency of initiations emitted was greater for two participants during the device‐visible condition, greater for another participant during the device‐not‐visible condition, and no difference as a function of auditory script location for the fourth participant. These results suggest that fading an auditory script played behind a child's head may be equally as effective for establishing stimulus control by target items as fading an auditory script initially attached to items.